Reflecting on Social Learning Tools to Enhance the Teaching-Learning Experience of Generation Z Learners - Cilliers, Elizelle Juanee (Frontiers in Education, 2021)
Limited research has considered social learning tools and preferences of the Generation Z learner from a higher educational perspective. This research is based on the educational theories of constructivism and social learning, in attempt to reflect on social learning tools employed in a third year Urban and Regional Planning module at the North-West University (South Africa). The empirical investigation was based on the reflections from Generation Z learners who were introduced to a range of social media tools. The paper aimed to investigate if social learning tools can positively impact the learner experience in the contemporary classroom based on longitudinal data. It identified the preferences of the Generation Z learners in terms of social media tools, and the trends thereof, during a 10-year period (2011 – 2020). Finally, the paper drew on the perspective of the educator, in reflecting on the challenges, but also scope, to include social learning tools as part of higher education teaching-learning.